Dampak Teknologi Digital Terhadap Evolusi Desain Arsitektur - Poltak, Hendrik; Peter Ardianto (UNIVERSITAS STEKOM, 2024)
The development of digital technology has significantly influenced the advancement of science and various other aspects. The realm of architectural design, both in the professional and educational fields, is not exempt from the influence of digital technology. Despite the fact that some architects still utilize traditional methods, digital technology has shifted traditional methods in architectural design. This writing aims to examine the role of digital technology in the world of architectural design. The method employed in this writing involves a literature review of several related studies. From the conducted review, it can be concluded that digital technology has made the architectural design process more efficient and straightforward. Additionally, with digital technology, architects can explore geometrical forms with high complexity. This is possible because computers nowadays are not merely used as tools to produce drawings or expedite the design process (computerization), but they actively play a role and are integrated into the architectural design process (computation).